The role of early-onset-sepsis in the neurodevelopment of very low birth weight infants - Tjark Ortgies; Michael Rullmann; Dorothée Ziegelhöfer; Annett Bläser; Ulrich H. Thome (BMC, 2021)
Abstract Aims The study investigated a putative association between early-onset-sepsis (EOS) and poor neurodevelopmental outcomes at 2 years corrected age in very low birth weight infants. Methods This was a single-center cohort study on infants weighing less than 1500 g with a gestational age below 35 weeks at birth born between 2008 and 2011. Neurodevelopmental outcomes were assessed at follow-up with the Bayley Scales of Infant Development-II. EOS was defined as either culture-proven EOS or clinical EOS using blood culture, CrP levels, and clinical symptoms and treatment. Neurodevelopmental impairment (NDI) was defined as one or more of the following: Mental Developmental Index (MDI) and/or Psychomotor Developmental Index (PDI) scores lower than 70; presence of cerebral palsy. Results Of 405 eligible newborns in the study period 166 were included. Two had culture-proven and 29 clinical EOS. Median MDI scores in patients with EOS were 96 (IQR: 86-106) and in the control group 94 (84-106, p = 0.77). PDI scores in patients with EOS were 96 (86-106) and in the control group 99,5 (92-103, p = 0.03). Of infected patients 7/31 (24%) showed NDI as defined, whereas only 11/135 (8%) showed NDI in the control group (OR 3.3, p = 0.03). Multiple regression analyses identified chorioamnionitis and poor CRIB-Scores as individual risk factors for MDI or PDI values < 70. Conclusion In our study, EOS among VLBW-infants significantly impaired the neurodevelopment at 2 years corrected age. As shown in previous reports infection continues to be a problem and strategies for a reduction need further improvement.